Fully functional HLA B27-restricted CD4+ as well as CD8+ T cell responses in TCR transgenic mice. - Roddis, M; Carter, R; Sun, M; Weissensteiner, T; Mcmichael, A; Bowness, P; Bodmer, H (2004)
The strong association of HLA B27 with spondyloarthropathies contrasts strikingly with most autoimmune diseases, which are HLA class II associated and thought to be mediated by CD4+ T lymphocytes. By introducing a human-derived HLA B27-restricted TCR into HLA B27 transgenic mice, we have obtained a functional TCR transgenic model, GRb, dependent on HLA B27 for response. Surprisingly, HLA B27 supported CD4+ as well as CD8+ T cell responses in vivo and in vitro. Further, HLA B27-restricted CD4+ T cells were capable of differentiation into a range of Th1 and Th2 T cell subsets with normal patterns of cytokine expression. The transgenic T cells were also able to enhance clearance of recombinant vaccinia virus containing influenza nucleoprotein in vivo. This is the first description of a human HLA class I-restricted TCR transgenic line. The existence of CD4+ MHC class I-restricted T cells has significant implications for immune regulation in autoimmunity and, in particular, in HLA B27-associated arthritis. We believe that this model provides a novel system for the study of unusual T cell behavior in vivo.